Enhancing the Professional Competence of Vocational School Teachers Through a Knowledge Management System-Based Training Model - Ali, Gunawan; Sonia Yulia Friska; Vitriani; Efendi, Raimon (Jurnal Penelitian dan Pengembangan Pendidikan, 2023)
The role of the Computer Network Engineering MGMP forum could have been more optimal in developing professional competence. If one pays attention to the usefulness of this forum, it is essential to support the improvement and development of the professional competence of SMK Computer Network Engineering teachers. This research aims to develop a Knowledge Management System-Based Training Model to improve the professional competence of vocational teachers. This research is research and development. This study uses the ADDIE development procedure. The subjects of this study were 35 teachers at SMK Computer Network Engineering Skills. The methods used to collect data are interviews and questionnaires. The data collection instrument uses a questionnaire sheet. The data analysis technique for this research is descriptive statistics. The results of this study, namely the needs analysis, show the level of need for this training model is 83.65%. The syntax of this model is an introduction, demonstration, discussion, B-KMS training, and evaluation. Products consisting of training models in book form; implementation of activity in the form of a guidebook; training materials in book form; use of applications in the form of books for admins and users; knowledge management system application. The study results show that this training model is valid, practical, effective and appropriate for use to improve teachers' professional competence.